2009
DOI: 10.1161/strokeaha.108.531616
|View full text |Cite
|
Sign up to set email alerts
|

Danqi Piantang Jiaonang (DJ), a Traditional Chinese Medicine, in Poststroke Recovery

Abstract: Background and Purpose-Stroke is a leading cause of death and disability worldwide. Despite improvements in acute stroke treatment, many patients only make a partial or poor recovery. Therefore, there is a need for treatments that would further improve outcome. Danqi Piantang Jiaonang (DJ; NeuroAid), a traditional Chinese medicine widely used in China to improve recovery after stroke, has been compared with another traditional Chinese medicine in 2 unpublished randomized clinical trials. The results of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 5 publications
3
88
0
Order By: Relevance
“…This is consistent with previously published studies on MLC601, which detected improved functional outcomes and motor recovery among mainly nonacute ischemic stroke patients. 11,12,14 These findings support the possible neurorestorative effects of MLC601 and would be topics of interest for further nonclinical and clinical investigations.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This is consistent with previously published studies on MLC601, which detected improved functional outcomes and motor recovery among mainly nonacute ischemic stroke patients. 11,12,14 These findings support the possible neurorestorative effects of MLC601 and would be topics of interest for further nonclinical and clinical investigations.…”
Section: Discussionsupporting
confidence: 55%
“…Because previous studies on MLC601 suggested a benefit in nonacute ischemic stroke patients, [11][12][13][14][15][16][17] the time window of 72 hours was chosen for this study in an attempt to test both the neuroprotective and neurorestorative properties of MLC601.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous clinical studies performed in China have shown that Neuroaid enhances stroke patients’ recovery from their neurological disability and improves functional outcome and thus, may be beneficial in post-stroke rehabilitation [7]. However, these trials did not comply with the International Conference on Harmonization/Good Clinical Practice guidelines and used positive controls.…”
Section: Introductionmentioning
confidence: 99%